Challenges to Physicians: Hospital Immunity and Sham Peer Review - Poston, Robert; Gharagozloo, Farid; W.G. Gruessner, Rainer (Journal of Human Psychology, 2023)
An opinion essay examines hospital immunity doctrines and alleged sham peer review, outlining legal context, patient‑safety implications, and avenues for due process.
Keywords: Hospital Immunity; Sham Peer Review; Due Process; Patient Safety; Physicians